Model Perencanaan Sumber Daya Manusia Serta Repositioning Dalam Pengembangan Sumber Daya Manusia: Suatu Kajian Literatur - Edi Irawan (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This article aims to review and attempt to confirm the concept of the resource planning model and repositioning in human resource development. The research method used is qualitative and literature studies or library research. Based on the results and discussion, it can be concluded theoretically that to understand the human resource planning model and positioning in human resource developmnet requires several important things including: (a) getting to know various models of human resource planning, such as the HR planning model by Andrew E Sikula, the Battelle Socio - Economic HR from Vetter and the HR planning Model from R.Wayne Mondy and Robert M. Noe, (b) Recognize and understand the various benefits of human resource planning, (c ) Implications of HR role repositioning HR, (d) Achievement of HR strategic role